(untitled) (Journal of Hama University, 2019)
The study was carried out in Damascus Countryside on (40) head horses race, including (20) head was used as a control group, and (20) head of horses given the group of vitamins AD3E (experiment). To study the effect of giving the group of vitamins AD3E on the blood concentration of glucose, cholesterol and calcium, after all horses were performed 1600 m race. Blood samples were collected from the jugular vein for all horses in both groups and at a sample rate per day during the two days before the race until the day after the race ended. The results of laboratory tests for serum samples showed a significant increase (p <0.05) in the concentration of glucose and cholesterol and a significant decrease (p <0.05) in the concentration of calcium in the control group immediately after the race ended, while in the group that given the vitamins AD3E led to maintain the stability of previous concentrations within good natural limits. In conclusion, it is important to measuring the concentration of glucose, cholesterol and calcium in the blood of race horses before and after sports competitions, and it is necessary to provide the group of vitamins AD3E for horses before these competitions because of its vital role in maintaining the previous concentrations within the normal natural limits. This can give the owners of Race horses to reduce the burdens of sports stress on their horses and maintain the activity and effectiveness of these horses during sports competitions.